Biaxially oriented polyamide film

A biaxially stretched polyamide film with a dispersed resin composition addresses strength and stability issues, ensuring effective ethanol permeability and resistance, suitable for alcohol transpiration agents and freshness-preserving packaging.

JP7619530B1Active Publication Date: 2025-01-22TOYOBO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024529851
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-30
Filing Date
2024-03-21
Publication Date
2025-01-22
Estimated Expiration
2044-03-21

AI Technical Summary

Technical Problem

Existing biaxially stretched polyamide films used for alcohol transpiration agents and freshness-preserving packaging face issues with reduced strength, bending pinhole resistance, and dimensional stability while maintaining ethanol permeability.

Method used

A biaxially stretched polyamide film containing polyamide 6 as the main component with a dispersed resin other than polyamide 6, achieving specific crystallinity, plane orientation, and a balanced resin composition to enhance bending pinhole resistance, puncture strength, and ethanol permeability.

Benefits of technology

The film exhibits excellent bending pinhole resistance, puncture strength, and dimensional stability, with ethanol permeability suitable for maintaining food freshness and reducing ethanol condensation, while being resource-efficient and reducing waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619530000005
    Figure 0007619530000005
  • Figure 0007619530000001
    Figure 0007619530000001
  • Figure 0007619530000002
    Figure 0007619530000002
Patent Text Reader

Abstract

The present invention aims to provide a biaxially oriented polyamide film that is excellent in bending pinhole resistance, puncture strength, dimensional stability, and ethanol permeability. The present invention relates to a biaxially oriented polyamide film that contains polyamide 6 as a main component and has an ethanol permeability of 6000 to 10000 g μm / m. 2 24hr (50%RH / 40℃), thickness is 15μm or less, thermal shrinkage in both the machine direction and width direction of the film is 2.0% or less, surface crystallization parameter is in the range of 1.0~1.5, and puncture strength is 6.0N or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biaxially oriented polyamide film suitable for use as a food packaging film, a packaging material for alcohol-evaporating agents, etc. [Background technology]

[0002] Biaxially stretched films made of aliphatic polyamides, such as polyamide 6, are excellent in impact resistance and pinhole resistance due to bending, and are widely used as various packaging film materials. In Patent Documents 1 and 2, polyamide films are generally used as base films for packaging bags for alcohol-evaporating agents and freshness-preserving packaging bags, which require specific gas permeability, because they have high alcohol permeability. In Patent Document 3, it is described that the desired gas permeability can be obtained by reducing the thickness of the biaxially stretched polyamide film. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-211604 A [Patent Document 2] JP 2002-204652 A [Patent Document 3] JP 2010-167652 A Summary of the Invention [Problem to be solved by the invention]

[0004] Patent Document 3 shows that reducing the thickness of the nylon film is effective in improving ethanol permeability, but the inventors found that reducing the film thickness leads to problems of reduced pinhole resistance and puncture strength. Patent Document 3 also found that there is room for improvement in the dimensional stability of the film.

[0005] An object of the present invention is to provide a biaxially oriented polyamide film which is excellent in bending pinhole resistance, puncture strength, dimensional stability, and ethanol permeability. [Means for solving the problem]

[0006] As a result of intensive research to achieve the above object, the present inventors have found that a biaxially stretched polyamide film having good pinhole resistance, puncture strength, dimensional stability, and ethanol permeability can be obtained by dispersing a resin other than polyamide 6 having a maximum dispersion diameter of 1 μm or more in a polyamide 6 resin and imparting a specific degree of planar orientation and a specific degree of crystallinity. The inventors have further researched and made improvements, and have completed the following representative inventions.

[0007] [1] A biaxially oriented polyamide film containing polyamide 6 as the main component, and having an ethanol permeability of 6000 to 10000 g μm / m 2 A biaxially oriented polyamide film having a thickness of 15 μm or less, a thermal shrinkage rate of 2.0% or less in both the machine direction and the width direction of the film when heat-treated for 10 minutes at 160°C for 24 hr (50% RH / 40°C), a surface crystallization parameter of 1.0 to 1.5, and a puncture strength of 6.0 N or more. [2] The biaxially stretched polyamide film according to [1], which has at least one layer containing 60% by mass or more and 99% by mass or less of a polyamide 6 resin (a) and 2% by mass or more and 40% by mass or less of a resin other than polyamide 6 (b). [3] The biaxially stretched polyamide film according to [2], wherein the resin (b) other than polyamide 6 is at least one selected from the group consisting of thermoplastic elastomers such as polyolefins, ionomer polymers, polyester-based elastomers, polyamide-based elastomers, polyolefin-based elastomers, polystyrene-based elastomers, polyurethane-based elastomers, and polyvinyl chloride-based elastomers, aliphatic polyester resins, aliphatic-aromatic polyester resins, aliphatic polyamide resins, and aliphatic-aromatic polyamide resins. [4] The biaxially oriented polyamide film according to either [2] or [3], wherein the aliphatic aromatic polyester resin is a polybutylene adipate terephthalate resin. [5] The biaxially stretched polyamide film according to [2], wherein the resin (b) other than polyamide 6 is derived from biomass and is at least one polyamide selected from the group consisting of polyamide 11, polyamide 410, polyamide 610, and polyamide 1010. [6] The biaxially stretched polyamide film according to any one of [2] to [5], wherein the maximum dispersion diameter of the resin (b) other than polyamide 6 is 1 μm or more. [7] The biaxially stretched polyamide film according to any one of [1] to [6], wherein the stress at 5% elongation in both the machine direction and the width direction of the film is 70.0 MPa or less. [8] The biaxially stretched polyamide film according to any one of [1] to [7], having a planar orientation degree (ΔP) of 0.050 or more. [9] The biaxially stretched polyamide film according to any one of [1] to [8], wherein a laminate film of the biaxially stretched polyamide film and a 40 μm-thick polyethylene film is prepared, and is flexed 1,000 times in an atmosphere at a temperature of 1° C. using a Gelbo flex tester. When the flexure is subjected to a flexing treatment, the number of pinholes generated is 20 or less.

[10] A food packaging material comprising the biaxially stretched polyamide film according to any one of [1] to [9] and a sealant film.

[11] A packaging material for an ethanol evaporative agent, comprising a laminate including at least two layers of the biaxially oriented polyamide film according to any one of [1] to [9] and a breathable resin film or nonwoven fabric. Effect of the Invention

[0008] The present invention can provide a biaxially oriented polyamide film having excellent bending pinhole resistance, puncture strength, dimensional stability, and ethanol permeability, as well as a food packaging material and an ethanol evaporative packaging material using the biaxially oriented polyamide film. [Brief description of the drawings]

[0009] [Figure 1] 1 is a transmission electron microscope photograph showing the dispersion state of polyamide 6 resin (a) and a resin other than polyamide 6 (b) contained in a film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The biaxially stretched polyamide film of the present invention will be described in detail below. In this specification, a numerical range expressed with "to" means a range including the numerical values ​​before and after "to" as the lower and upper limits.

[0011] The biaxially stretched polyamide film of the present invention preferably contains polyamide 6 as a main component. Here, "containing polyamide 6 as a main component" means that the content of the component in the polyester resin composition constituting the film is 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, based on 100% by mass of all the components of the polyester resin. The biaxially stretched polyamide film of the present invention is preferably a biaxially stretched polyamide film having a functional layer laminated on at least one side of a substrate layer. The biaxially stretched polyamide film of the present invention is preferably a film having at least two layers, a substrate layer and a functional layer, and may have a two-layer structure of substrate layer / functional layer or a three-layer structure of functional layer / substrate layer / functional layer. Each layer will be described in detail below.

[0012] [Base material layer A] The first resin composition forming the base layer contains at least polyamide 6 resin (a). The first resin composition contains preferably 60% by mass or more of polyamide 6, more preferably 80% by mass or more, and even more preferably 85% by mass or more, based on 100% by mass of the first resin composition. If the content of polyamide 6 is less than 60%, the impact resistance may decrease and the gas permeability may increase significantly. By containing 80% by mass or more of polyamide 6, a polyamide film having mechanical strength such as impact strength and gas barrier properties can be obtained. The upper limit of the content of polyamide 6 is preferably 98% by mass or less, more preferably 97% by mass or less, based on 100% by mass of the first resin composition. That is, polyamide 6 is preferably 60 to 98% by mass, more preferably 80 to 98% by mass, and even more preferably 85 to 97% by mass. In this specification, the upper and lower limits of the numerical range may be appropriately combined to form a suitable numerical range (hereinafter, the same applies to the numerical range).

[0013] The first resin composition forming the base layer contains at least one type of resin (b) other than polyamide 6. The resin (b) is a substance that has the effect of imparting flexibility to the base layer and is not particularly limited as long as it is incompatible with polyamide 6, but is preferably at least one type selected from the group consisting of thermoplastic elastomers such as polyolefins, ionomer polymers, polyester-based elastomers, polyamide-based elastomers, polyolefin-based elastomers, polystyrene-based elastomers, polyurethane-based elastomers, and polyvinyl chloride-based elastomers, aliphatic polyester resins, aliphatic aromatic polyester resins, aliphatic polyamide resins, and aliphatic aromatic polyamide resins.

[0014] Examples of polyolefins include homopolymers of olefins, copolymers of olefins and other monomers, and mixtures thereof, and polyolefins graft-polymerized with unsaturated carboxylic acids. Examples of homopolymers of olefins include polyethylene (high density, low density) and polypropylene. Examples of copolymers of olefins and other monomers include ethylene-vinyl acetate copolymers, ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-acrylic acid copolymers, and ethylene-methacrylic acid copolymers. Examples of unsaturated carboxylic acids used in graft-polymerization of unsaturated carboxylic acids to polyolefins include carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, and citraconic acid, and acid anhydrides such as maleic anhydride, citraconic anhydride, and itaconic anhydride. The unsaturated carboxylic acids may be used alone or in combination.

[0015] An ionomeric polymer is composed of a polyolefin and an α,β-ethylenically unsaturated monomer having a carboxyl moiety, and the carboxyl moiety is neutralized with a metal ion having a valence of 1 to 3. Examples of polyolefins include copolymers of polyethylene or ethylene with at least one α-olefin having usually 3 to 8 carbon atoms and a diolefin, such as 1,4-hexadiene. Examples of α,β-ethylenically unsaturated monomers having a carboxyl moiety include methacrylic acid, acrylic acid, maleic acid, maleic anhydride, and fumaric acid. Examples of metal ions include zinc ions, sodium ions, lithium ions, potassium ions, and magnesium ions. Ionomeric polymers are produced by a direct synthesis method in which an α-olefin and an olefin monomer having a carboxyl moiety are polymerized, or a grafting method in which a monomer having a carboxyl moiety is added to an olefin skeleton.

[0016] Examples of the thermoplastic elastomer include thermoplastic elastomers such as polyolefin, ionomer polymer, polyester elastomer, polyamide elastomer, polyolefin elastomer, polystyrene elastomer, polyurethane elastomer, polyvinyl chloride elastomer, aliphatic polyester resin, aliphatic aromatic polyester resin, aliphatic polyamide resin, and aliphatic aromatic polyamide resin. For example, polyamide elastomer, polyester elastomer, polyurethane elastomer, acrylic thermoplastic elastomer, polystyrene elastomer, and hydrogenated products thereof may be used.

[0017] Examples of the polyamide elastomer include polyether amide, polyether ester amide, and polyester amide. The polyamide elastomer may be copolymerized with a dicarboxylic acid such as dodecanedicarboxylic acid, adipic acid, or terephthalic acid as an optional component.

[0018] The polyester elastomer refers to a block copolymer composed of a hard segment having crystallinity and a soft segment having flexibility. Among them, a block copolymer having a hard segment made of a cyclic polyester and a soft segment made of a polyalkylene ether, and a block copolymer having a hard segment made of a cyclic polyester and a soft segment made of a linear aliphatic polyester are preferred, and a cyclic polyester-polyalkylene ether block copolymer is more preferred. In the present invention, the term "cyclic polyester" refers to a raw material dicarboxylic acid or its alkyl ester containing a dicarboxylic acid or its alkyl ester having a cyclic structure.

[0019] From the viewpoint of moldability, the polyurethane-based thermoplastic elastomer may have a hard segment consisting of a diisocyanate compound and a glycol having a molecular weight of about 50 to 500, and a soft segment consisting of a diisocyanate compound and a long-chain glycol. As the long-chain glycol, a polyether-based one such as a polyalkylene glycol having a molecular weight of about 500 to 10,000, or a polyester-based one such as a polyalkylene adipate, polycaprolactone, or polycarbonate is used. In addition, as the diisocyanate compound, phenylene diisocyanate, trigen diisocyanate, xylene diisocyanate, 4,4-diphenylmethane diisocyanate, and hexamethylene diisocyanate may be used. The diisocyanate compound may be the same or different in the soft segment and the hard segment.

[0020] Examples of the acrylic thermoplastic elastomer include ethylene-acrylic ester copolymer elastomer, ethylene-methacrylic ester copolymer elastomer, and acrylic ABA type triblock copolymer consisting of acrylic ester and methacrylic ester.

[0021] Examples of the polystyrene-based elastomer include styrene-butadiene copolymer rubber and styrene-isoprene copolymer rubber.

[0022] As the aliphatic polyester resin, polybutylene succinate and polybutylene succinate adipate are preferably used. As the aliphatic aromatic polyester resin, an aliphatic aromatic polyester resin containing an adipic acid component is preferable, and polybutylene adipate terephthalate is particularly preferable. More preferable is an aliphatic or aliphatic aromatic polyester resin having a glass transition temperature (Tg) of -30°C or less. By using a polyester copolymer having a glass transition temperature of -30°C or less, excellent pinhole resistance can be achieved even in a freezing environment.

[0023] As the aliphatic polyamide resin, polyamide 11, polyamide 610, polyamide 1010 and polyamide 410 are preferably used. Furthermore, the polyamide resin may be at least partly derived from biomass. By containing a polyamide resin containing a biomass-derived raw material, the bending pinhole resistance can be further improved. Examples of the aliphatic aromatic polyamide resin include polymetaxylylene adipamide (MXD6), polyamide 6T, polyamide 6I, polyamide 6T6I, and polyamide 9T. Among these, MXD6 is suitable from the viewpoint of improving stretchability and adhesiveness.

[0024] The content of the resin (b) other than polyamide 6 contained in the first resin composition forming the base layer is preferably 2% by mass to 40% by mass or less, or 20% by mass or less, more preferably 4% by mass to 15% by mass, based on 100% by mass of the first resin composition. By containing 2% by mass or more of the resin (b) other than polyamide 6, it is possible to obtain the effect of pinhole resistance against bending. By containing 40% by mass or less, preferably 20% by mass or less of the resin (b) other than polyamide 6, it is possible to prevent the film from becoming soft, and the puncture strength and impact strength from decreasing. In addition, the film becomes more stretchable, and it is also possible to prevent pitch deviation during processing such as printing.

[0025] The first resin composition forming the base layer may contain a thermoplastic resin other than polyamide 6 resin, provided that the object of the present invention is not impaired. Examples of the thermoplastic resin include polyamide-based resins such as polyamide 12 resin, polyamide 66 resin, polyamide 6·12 copolymer resin, polyamide 6·66 copolymer resin, polyamide MXD6 resin, polyamide MXD10 resin, and polyamide 11·6T copolymer resin. If necessary, a thermoplastic resin other than polyamide-based resin, such as a polyester-based polymer such as polyethylene terephthalate, polybutylene terephthalate, or polyethylene-2,6-naphthalate, or a polyolefin-based polymer such as polyethylene or polypropylene, may be contained.

[0026] The base layer may contain various additives, such as other thermoplastic resins, lubricants, heat stabilizers, antioxidants, antistatic agents, anti-fogging agents, ultraviolet absorbers, dyes, and pigments, as required.

[0027] [Functional layer B] The second resin composition forming the functional layer preferably contains at least polyamide 6. The second resin composition preferably contains 70% by mass or more of polyamide 6, more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on 100% by mass of the second resin composition. By containing 70% by mass or more of polyamide 6, a polyamide film having mechanical strength such as impact strength and gas barrier properties can be obtained. The upper limit of the content of polyamide 6 is preferably 99% by mass or less, more preferably 96% by mass or less, based on 100% by mass of the first resin composition. That is, the content of polyamide 6 is preferably 70 to 99% by mass, more preferably 80 to 96% by mass, and even more preferably 90 to 96% by mass. The polyamide 6 may be the same as the polyamide 6 used in the first resin composition.

[0028] The second resin composition forming the functional layer may contain a polyamide resin other than polyamide 6. Examples of polyamide resins other than polyamide 6 include polyamide MXD6 resin, polyamide 11, polyamide 12, and polyamide 66. When the second resin composition contains a polyamide resin other than polyamide 6, the content is preferably 1% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 20% by mass or less, and particularly preferably 5% by mass or more and 10% by mass or less, based on 100% by mass of the second resin composition. By containing 1% by mass or more, it is possible to impart slipperiness to the film. On the other hand, if the content is more than 30% by mass, the effect of improving the slipperiness of the film may be saturated. As the polyamide resin other than polyamide 6, polyamide MXD6 resin is preferably used.

[0029] The second resin composition forming the functional layer can contain fine particles, organic lubricants, etc. as lubricants to improve the film's slipperiness. By improving the slipperiness, the film can be made easier to handle and the risk of packaging bags breaking due to friction can be reduced.

[0030] The fine particles can be appropriately selected from inorganic fine particles such as silica, kaolin, zeolite, etc., polymeric organic fine particles such as acrylic and polystyrene, etc. From the viewpoints of transparency and slipperiness, it is preferable to use silica fine particles.

[0031] The average particle size of the fine particles is preferably 0.5 μm or more and 5.0 μm or less, more preferably 1.0 μm or more and 3.0 μm or less. When the average particle size is 0.5 μm or more, good slipping properties can be expected, and when the average particle size is 5.0 μm or less, it is expected to prevent poor appearance due to increased surface roughness of the film.

[0032] When silica fine particles are used as the fine particles, the pore volume of the silica is preferably in the range of 0.5 ml / g to 2.0 ml / g, more preferably 0.8 ml / g to 1.6 ml / g.

[0033] As the organic lubricant, fatty acid amide and / or fatty acid bisamide can be used. Examples of fatty acid amide and / or fatty acid bisamide include erucic acid amide, stearic acid amide, ethylene bisstearic acid amide, ethylene bisbehenic acid amide, and ethylene bisoleic acid amide. The content of fatty acid amide and / or fatty acid bisamide contained in the second resin composition forming the functional layer is preferably 0.01% by mass or more and 0.40% by mass or less, and more preferably 0.05% by mass or more and 0.30% by mass or less, based on 100% by mass of the second resin composition. By being 0.01% by mass or more, the effect of slipping can be expected. By being 0.40% by mass or less, the wettability of the printing ink when a printing layer is provided on the functional layer side can be ensured.

[0034] The functional layer may contain various additives such as other thermoplastic resins, lubricants, heat stabilizers, antioxidants, antistatic agents, anti-fogging agents, ultraviolet absorbers, dyes, and pigments.

[0035] [Biaxially oriented polyamide film] The biaxially stretched polyamide film of the present invention is preferably a film having at least two layers, a substrate layer and a functional layer, and may have a two-layer structure of substrate layer / functional layer or a three-layer structure of functional layer / substrate layer / functional layer.

[0036] The ethanol permeability of the biaxially oriented polyamide film of the present invention is 6000 g μm / m 2 ·24hr (50%RH / 40℃) or more. When the biaxially stretched polyamide film of the present invention is used as a packaging material for ethanol transpiration agents, the ethanol impregnated into the nonwoven fabric as an ethanol transpiration agent slowly transpires, and a sufficient ethanol gas concentration can be obtained to maintain the freshness of food in the food packaging. The ethanol permeability is 6000g·μm / m 2 If it is less than 24hr (50%RH / 40℃), the permeation of the alcohol gas evaporating from the alcohol evaporating agent is inhibited, and it is not desirable to obtain a sufficient alcohol gas concentration to keep the food fresh inside the food packaging. The ethanol permeability is 10000g·μm / m 2 ·24hr (50% RH / 40℃) or less is preferable. 10000g·μm / m 2 By keeping the humidity at 50% RH / 40℃ or less for 24 hours, it is possible to prevent condensation of ethanol inside the package that would occur due to the increased amount of ethanol permeating through the package.

[0037] The thickness of the biaxially stretched polyamide film of the present invention is preferably 15 μm or less, more preferably 5 to 12 μm. By being 15 μm or less, the film has excellent alcohol permeability and contributes to resource saving and waste reduction. When the film is 5 μm or more, the film has a sufficient mechanical strength required for secondary processing such as lamination, coating, and slitting.

[0038] The thickness of the substrate layer is preferably 50% to 90%, particularly preferably 60% to 80%, of the total thickness of the substrate layer and the functional layer (when a plurality of substrate layers and functional layers are present, the total thickness of each layer) taken as 100%. By making the thickness of the substrate layer 50% or more, bending pinhole resistance can be imparted. By making the thickness of the substrate layer 90% or less, friction pinhole resistance can be imparted to the functional layer.

[0039] The biaxially stretched polyamide film of the present invention preferably has a stress at 5% elongation obtained by a tensile test in the machine direction and width direction of the film, i.e., an F5 value of 70 MPa or less. More preferably, it is 60 MPa or less, and even more preferably, it is 50 MPa or less. By making the F5 value 70 MPa or less, the film becomes flexible and is less likely to break due to bending fatigue. The lower limit of the F5 value is preferably 20 MPa or more. Making the F5 value 20 MPa or more is preferable in terms of preventing print pitch deviation due to film elongation during secondary processing. That is, the F5 value is preferably 20 to 70 MPa, more preferably 20 to 60 MPa, and even more preferably 20 to 50 MPa. Means for making the F5 value 20 MPa or more and 70 MPa or less include low-ratio stretching, high-temperature stretching, and addition of a resin other than nylon 6, and from the viewpoint of productivity, addition of a resin other than nylon 6 is preferable.

[0040] The biaxially stretched polyamide film of the present invention has excellent pinhole resistance when subjected to a twist bending test using a Gelbo flex tester 1000 times at a temperature of 1° C., and the number of pinhole defects is 1520 or less, more preferably 15 or less, and even more preferably 10 or less. The fewer the number of pinhole defects after the bending test, the better the pinhole resistance when bending. If the number of pinholes is preferably 1520 or less, more preferably 15 or less, a packaging bag that is less susceptible to pinholes even when a load is applied to the packaging bag during transportation, etc. can be obtained.

[0041] The biaxially stretched polyamide film of the present invention has a peak at 1200 cm in the spectrum obtained by ATR measurement of FT-IR. -1 Nearby and 1370cm -1 The crystallization parameter obtained from the intensity ratio of the peaks around 1200cm -1 / 1370cm -1 ) is preferably 1.0 or more. -1 The peak at 1370 cm is the absorption due to the α crystal of nylon 6. -1 is an absorption unrelated to crystallization. By setting this crystallization parameter in the range of 1.0 to 1.5, dimensional stability can be obtained. By setting the crystallization parameter to 1.0 or more, dimensional stability is improved. By setting the crystallization parameter to 1.5 or less, mechanical strength can be obtained.

[0042] The biaxially stretched polyamide film of the present invention preferably has a heat shrinkage rate at 160°C for 10 minutes in the range of 0.6% to 3.0% in both the machine direction (hereinafter sometimes abbreviated as MD direction) and the width direction (hereinafter sometimes abbreviated as TD direction), more preferably 0.5% to 2.0%. By having a heat shrinkage rate of 3.0% or less, it is possible to suppress the occurrence of curling or shrinkage when heat is applied in the next process such as lamination or printing. A heat shrinkage rate of 0.6% or more is preferable in terms of excellent impact resistance.

[0043] The planar orientation (ΔP) of the biaxially stretched polyamide film in the present invention is preferably 0.050 to 0.070. The planar orientation is determined by measuring the birefringence with a refractometer and calculating it from the following formula, where Nx is the refractive index in the longitudinal direction, Ny is the refractive index in the width direction, and Nz is the refractive index in the thickness direction. ΔP=(Nx+Ny) / 2-Nz The plane orientation can be increased by increasing the biaxial stretch ratio, particularly the stretch ratio in the TD direction, and a plane orientation of 0.05 or more can provide the film with mechanical strength such as puncture strength, while a plane orientation of 0.07 or less can suppress a decrease in productivity.

[0044] The impact strength of the biaxially oriented polyamide film of the present invention is preferably 0.6 J or more, and more preferably 0.7 J or more.

[0045] The puncture strength of the film of the present invention is preferably 6.0 N or more. By setting the puncture strength to 6.0 N or more, even when filled with solid contents, it is possible to prevent the contents from puncturing the bag and causing a hole in the bag, or to prevent the bag from being caused by an external factor during transportation. The upper limit of the puncture strength is not particularly limited, but may be 100 N or less, or may be 50 N or less.

[0046] The maximum dispersion diameter of the resin (b) other than polyamide 6 contained in the base layer is preferably 1.0 μm or more. Here, the maximum dispersion diameter refers to the longest length (unit: μm) of the major axis of the resin (b) dispersed in the base layer when the base layer is observed with a transmission electron microscope (TEM). An example is shown in FIG. 1. FIG. 1 is a photograph of a cross section of the film in the machine direction observed with a transmission electron microscope at a magnification of 2000 times, and the darkly stained domain is the resin (b). By having the dispersion diameter of the resin (b) be 1.0 μm or more, good bending pinhole resistance and ethanol permeability are obtained. The reason for good bending pinhole resistance is believed to be that the dispersion of flexible resin (b), which is incompatible with polyamide 6, improves the flexibility of the entire film, making it less susceptible to destruction due to bending fatigue.The reason for good ethanol permeability is believed to be that the dispersion of resin (b), which is incompatible with polyamide 6, in polyamide 6 forms an interface with weak adhesion between polyamide 6 and resin (b), allowing ethanol to permeate the film through this interface. When the maximum dispersion diameter of resin (b) is less than 1.0 μm, compatibility is promoted and the characteristics of the base material, polyamide 6, become apparent, resulting in a decrease in pinhole resistance and ethanol permeability.

[0047] [How to make biaxially oriented polyamide film] The method for producing the biaxially stretched polyamide film of the present invention will now be described. First, the raw resin is melt-extruded using an extruder, extruded into a film shape from a T-die, cast onto a cooling roll and cooled to obtain an unstretched film in which at least a base layer and a functional layer are laminated. In order to obtain an unstretched laminated film, a co-extrusion method using a feed block or a multi-manifold is preferable. In addition to the co-extrusion method, a dry lamination method, an extrusion lamination method, etc. can also be selected. When laminating by the co-extrusion method, it is desirable to make the difference in melt viscosity between the first resin composition forming the base layer and the second resin composition forming the functional layer small.

[0048] The melting temperature of the resin is preferably 220°C or more and 350°C or less. If it is less than the above, unmelted matter may occur, and defects such as poor appearance may occur, while if it exceeds the above, deterioration of the resin may be observed, and molecular weight reduction and deterioration of appearance may occur. The die temperature is preferably 250°C or more and 350°C or less. The cooling roll temperature is preferably -30°C or more and 80°C or less, and more preferably 0°C or more and 50°C or less. To obtain an unstretched film by casting and cooling a film-like melt extruded from a T-die onto a rotating cooling drum, for example, a method using an air knife or an electrostatic adhesion method in which a static charge is applied can be preferably applied. In addition, it is preferable to cool the opposite side of the cooling roll of the cast unstretched film. For example, it is preferable to use a method of contacting the opposite side of the cooling roll of the unstretched film with a cooling liquid in a tank, a method of applying a liquid that evaporates with a spray nozzle, a method of spraying a high-speed fluid, and the like in combination. The unstretched film obtained in this way is stretched in a biaxial direction to obtain the biaxially stretched polyamide film of the present invention.

[0049] The stretching method may be either a simultaneous biaxial stretching method or a sequential biaxial stretching method. The sequential biaxial stretching method is preferable because it is advantageous in that the degree of planar orientation is increased and piercing strength is easily obtained, the crystallization parameters are easily adjusted to obtain the desired dimensional stability, and the film-forming speed is easily increased, which makes it easy to reduce production costs. In either case, multi-stage stretching such as one-stage stretching or two-stage stretching can be used as the stretching method in the MD direction. As described later, multi-stage MD stretching such as two-stage stretching is preferable in terms of physical properties and uniformity of physical properties in the MD and TD directions (isotropy) rather than one-stage stretching. Roll stretching is preferable for stretching in the MD direction in the sequential biaxial stretching method.

[0050] The lower limit of the stretching temperature in the MD direction is preferably 50°C, more preferably 55°C, and even more preferably 60°C. If it is less than 50°C, the resin does not soften and stretching may be difficult. The upper limit of the stretching temperature in the MD direction is preferably 120°C, more preferably 115°C, and even more preferably 110°C. If it exceeds 120°C, the resin may become too soft and stable stretching may not be possible. Stretching at 120°C or less is preferable in terms of preventing sticking to the roll and breakage. That is, the stretching temperature in the MD direction is preferably 50 to 120°C, more preferably 55 to 115°C, and even more preferably 60 to 110°C.

[0051] The lower limit of the stretching ratio in the MD direction (when stretching in multiple stages, the total stretching ratio multiplied by each stretching ratio) is preferably 2.2 times, more preferably 2.5 times, and even more preferably 2.8 times. If it is less than 2.2 times, the thickness accuracy in the MD direction decreases, and the crystallinity becomes too low, so that the impact strength decreases. The upper limit of the stretching ratio in the MD direction is preferably 5.0 times, more preferably 4.5 times, and most preferably 4.0 times. A stretching ratio of 5.0 times or less is preferable from the viewpoint of achieving both productivity and film formation stability. That is, the stretching ratio in the MD direction is preferably 2.2 to 5.0 times, more preferably 2.5 to 4.5 times, and even more preferably 2.8 to 4.0 times.

[0052] In addition, when the MD stretching is performed in multiple stages, the above-mentioned stretching is possible in each stretching, but it is preferable to adjust the stretching ratio so that the product of all MD stretching ratios is 5.0 or less. For example, in the case of two-stage stretching, it is preferable that the first stage stretching is 1.5 to 2.1 times, and the second stage stretching is 1.5 to 1.8 times.

[0053] The film stretched in the MD direction is stretched in the TD direction by a tenter, heat-set, and relaxed (also called relaxation treatment). The lower limit of the stretching temperature in the TD direction is preferably 50°C, more preferably 55°C, and even more preferably 60°C. If it is less than 50°C, the resin does not soften, and stretching may be difficult. The upper limit of the stretching temperature in the TD direction is preferably 190°C, more preferably 185°C, and even more preferably 180°C. It is preferable to set the stretching temperature in the TD direction to 190°C or less from the viewpoint of suppressing film crystallization and preventing breakage. That is, the stretching temperature in the TD direction is preferably 50 to 190°C, more preferably 55 to 185°C, and even more preferably 60 to 180°C.

[0054] The lower limit of the stretching ratio in the TD direction (when stretching in multiple stages, the total stretching ratio multiplied by each stretching ratio) is preferably 2.8 times, more preferably 3.2 times, even more preferably 3.5 times, and particularly preferably 3.8 times. If it is less than 2.8 times, the thickness accuracy in the TD direction decreases, and the crystallinity becomes too low, so that the impact strength decreases. The upper limit of the stretching ratio in the TD direction is preferably 5.5 times, more preferably 5.0 times, even more preferably 4.7 times, particularly preferably 4.5 times, and most preferably 4.3 times. It is preferable to set the stretching ratio in the TD direction to 5.5 times or less from the viewpoint of preventing breakage. That is, the stretching ratio in the TD direction is preferably 2.8 to 5.5 times, more preferably 3.2 to 5.0 times, even more preferably 3.5 to 4.7 times, particularly preferably 3.8 to 4.5 times, and most preferably 3.8 to 4.3 times.

[0055] The lower limit of the heat setting temperature is preferably 210°C, more preferably 212°C. If the heat setting temperature is low, the heat shrinkage rate becomes too large, which deteriorates the appearance after lamination and tends to reduce the laminate strength. The upper limit of the heat setting temperature is preferably 220°C, more preferably 218°C. If the heat setting temperature is too high, the impact strength tends to decrease. The heat setting time is preferably 0.5 to 20 seconds. It is further preferably 1 to 15 seconds. The heat setting time can be set to an appropriate time in consideration of the heat setting temperature and the wind speed in the heat setting zone. It is preferable to set the heat setting temperature to 220°C or less from the viewpoint of preventing the embrittlement of the film. It is preferable to set the heat setting temperature to 210°C or more from the viewpoint of improving the dimensional stability and the laminate strength. That is, the heat setting temperature is preferably 210 to 220°C, more preferably 212 to 218°C.

[0056] Performing a relaxation treatment after heat setting is effective in controlling the heat shrinkage rate. The temperature for the relaxation treatment can be selected within the range from the heat setting temperature to the Tg of the resin, but is preferably (heat setting temperature (°C) - 10) °C or higher (Tg (°C) + 10) °C or lower. If the relaxation temperature is too high, the shrinkage rate is too fast, which is not preferable, and may cause distortion. Conversely, if the relaxation temperature is too low, the film does not undergo relaxation treatment, but simply slackens, and the heat shrinkage rate does not decrease, resulting in poor dimensional stability. The lower limit of the relaxation rate in the relaxation treatment is preferably 0.5%, more preferably 1%. If it is less than 0.5%, the heat shrinkage rate may not decrease sufficiently. The upper limit of the relaxation rate is preferably 20%, more preferably 15%, and even more preferably 10%. If it exceeds 20%, sagging may occur in the tenter, making production difficult. A relaxation rate of 0.5% or higher is preferable in terms of reducing the heat shrinkage rate. A relaxation rate of 20% or lower is preferable in terms of preventing film sagging. That is, the relaxation rate is preferably 0.5 to 20%, more preferably 1 to 15%, and further preferably 1 to 10%.

[0057] Furthermore, the biaxially stretched polyamide film of the present invention can be subjected to heat treatment or humidity conditioning treatment to improve dimensional stability depending on the application. In addition, it can also be subjected to corona treatment, coating treatment, flame treatment, printing, deposition of metals, inorganic oxides, etc. to improve the adhesion of the film surface.

[0058] In one embodiment of the present invention, the biaxially oriented polyamide film of the present invention is processed into a laminated film by laminating a sealant film, thereby providing a packaging material. Examples of the sealant film include an unstretched linear low density polyethylene (LLDPE) film, an unstretched polypropylene (CPP) film, and an ethylene-vinyl alcohol copolymer resin (EVOH) film. The sealant film may be laminated so as to be in direct contact with the biaxially oriented polyamide film, or may be laminated via another layer such as an adhesive layer. The packaging material may include a printing layer. The packaging material of the present invention is made into a bag and processed into a packaging bag.

[0059] Another embodiment of the present invention provides a packaging material for ethanol transpiration agents, which is composed of a laminate including at least two layers of the biaxially oriented polyamide film of the present invention and a breathable resin film or nonwoven fabric. The breathable resin film is not particularly limited as long as it is a film having breathability or ethanol permeability, and examples thereof include unstretched linear low density polyethylene (LLDPE) film, unstretched polypropylene (CPP) film, ethylene-vinyl alcohol copolymer resin (EVOH) film, and ethylene-vinyl acetate copolymer resin (EVA) film. In addition, a nonwoven fabric can be used instead of or in combination with the breathable resin film. For example, polyester, polypropylene, rayon, nylon, biodegradable fiber, pulp, cotton, etc. may be used as the nonwoven fabric substrate, and polypropylene is preferably used. As the nonwoven fabric, either a short fiber nonwoven fabric or a long fiber nonwoven fabric can be used. The nonwoven fabric may be a paper substrate.

[0060] This application claims the benefit of priority based on Japanese Patent Application No. 2023-055926, filed on March 30, 2023. The entire contents of the specification of Japanese Patent Application No. 2023-055926, filed on March 30, 2023, are incorporated by reference into this application. EXAMPLES

[0061] The films were evaluated by the following measurement methods. Unless otherwise specified, the measurements were carried out in a measurement room with an environment of 23° C. and a relative humidity of 65%.

[0062] (1) Film thickness Divide the film into 10 equal parts in the TD direction (for narrow films, divide it so that the width is sufficient to measure the thickness), cut out 100mm films in the MD direction, and condition them for more than 2 hours in an environment with a temperature of 23℃ and a relative humidity of 65%. Using a thickness measuring device made by Tester Sangyo, measure the thickness at the center of each sample, and take the average value as the thickness.

[0063] (2) Thermal shrinkage rate of film The heat shrinkage rate was measured according to the following formula in accordance with the dimensional change test method described in JIS C2318, except that the test temperature was 160° C. and the heating time was 10 minutes. Heat shrinkage rate = [(length before treatment - length after treatment) / length before treatment] x 100 (%)

[0064] (3) F5 value of film The obtained biaxially stretched polyamide film was left to stand for 2 hours in a room adjusted to 23°C and 50% relative humidity, and then cut into strips of 150 mm (gauge length 100 mm) in the measurement direction of the film's MD and TD, and 15 mm in the direction perpendicular to the measurement direction to obtain samples. A tensile test was performed at a test speed of 200 mm / min using a tensile tester (Shimadzu Corporation AG-1I) equipped with a 1 kN load cell and a sample chuck. From the obtained stress-elongation curve, the stress when the sample was elongated by 5% was taken as the F5 value and treated as an alternative value for the elastic modulus. Measurements were performed on three samples, and the average value of each was calculated.

[0065] (4) Impact strength of film The measurement was carried out using a film impact tester manufactured by Toyo Seiki Seisakusho Co., Ltd.

[0066] (5) Film puncture strength Measurements were made in accordance with "2. Test methods for strength, etc." in the Food Sanitation Act's "Standards for Foods, Additives, etc., Part 3: Apparatus and Containers / Packaging" (Ministry of Health and Welfare Notification No. 20, 1982). A needle with a tip diameter of 0.7 mm was pierced into the film at a piercing speed of 50 mm / min, and the strength at which the needle penetrated the film was measured, which was taken as the piercing strength. Measurements were made at room temperature (23°C), and the value obtained was taken as the piercing strength (unit: N) of the film.

[0067] (6) Crystallization parameters FT-IR ATR measurements were performed on the front and back surfaces of the sample under the following conditions. FT-IR equipment: Bio Rad DIGILAB FTS-60A / 896 Single reflection ATR attachment: golden gate MKII (SPECAC) Internal reflective elements: Diamond Incident angle: 45° Resolution: 4cm -1 Number of times accumulated: 128 times The crystallinity is 1200 cm -1 Absorption near 1370cm -1 Intensity ratio of absorbance appearing near 1200cm -1 / 1370cm -1 ) where 1200 cm -1 is the absorption of α-crystal of nylon 6, 11370cm -1 is absorption unrelated to the crystal.

[0068] (7) Planar orientation of film The refractive index of the sample in the longitudinal direction (nx), width direction (ny), and thickness direction (nz) were measured using an Abbe refractometer with sodium D line as a light source according to JIS K 7142-1996 A method, and the plane orientation coefficient was calculated using formula (1). Plane orientation coefficient (ΔP) = (nx + ny) / 2 - nz

[0069] (8) Ethanol permeability The cotton soaked in ethanol was placed in a cup, the cup was covered with film, and the cup was left for 24 hours under conditions of 50% relative humidity and 40°C. The ethanol permeability was measured from the weight loss.

[0070] (9) Dispersion diameter of resin The film was cut so that the cross section in any direction could be observed, and embedded in epoxy resin. Ultrathin sections were prepared from the embedded samples using a microtome equipped with an ultrasonic knife. In order to confirm the dispersion shape of resin (b), appropriate staining treatment was performed according to the type of resin (b). Carbon deposition was performed on the test pieces to prepare samples for TEM observation. Observations and photographs were performed using a JEOL JEM2100 transmission electron microscope at an accelerating voltage of 200 kV. The magnification was adjusted so that the entire base layer was included in the photographed range. The longest major axis length of the resin dispersed in the base layer in the obtained photograph was taken as the maximum dispersion diameter.

[0071] (10) Pinhole resistance of film when bent The number of pinholes due to bending fatigue was measured by the following method using a Gelbo Flex Tester manufactured by Tester Sangyo Co., Ltd. Specifically, after applying a polyester-based adhesive to the biaxially oriented polyamide film manufactured in the examples, a linear low-density polyethylene film (L-LDPE film: manufactured by Toyobo Co., Ltd., L4102) having a thickness of 40 μm was dry-laminated, and aging was performed for 3 days in an environment of 40 ° C. to obtain a laminate film. The obtained laminate film was cut into 12 inches × 8 inches, and made into a cylindrical shape with a diameter of 3.5 inches. One end of the cylindrical film was fixed to the fixed head side of the Gelbo Flex Tester, and the other end was fixed to the movable head side, and the initial gripping distance was set to 7 inches. A bending fatigue was performed 1000 times at a speed of 40 times / min, in which a 440 degree twist was given in the first 3.5 inches of the stroke, and the entire stroke was completed in a linear horizontal motion for the next 2.5 inches, and the number of pinholes generated in the laminate film was counted. The measurement was performed in an environment of 1 ° C. The test film was placed on a filter paper (Advantec, No. 50) with the L-LDPE film side facing down, and the four corners were fixed with cellophane tape (registered trademark). Ink (Pilot ink (product number INK-350-Blue) diluted 5 times with pure water) was applied to the test film and spread over the entire surface using a rubber roller. After wiping off unnecessary ink, the test film was removed, and the number of ink dots on the filter paper was counted.

[0072] The following resin compositions were used for the base layer and the functional layer. Resin composition constituting base layer A: Polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220°C) Resins other than polyamide 6 (b) Polybutylene adipate terephthalate PBAT (BASF Ecoflex F-Blend C1200) Polyester elastomer PEE (Tefabloc TPC A1400N, manufactured by Mitsubishi Chemical Corporation) ·Polyamide elastomer PAE (Arkema PEBAX 4033 SA01) Polyolefin elastomer POE (Mersen H6051, manufactured by Tosoh Corporation) Polybutylene succinate PBS (Showa Polymer Co., Ltd., Bionolle 1001) Polyamide 11: (Arkema Rilsan, melting point 186°C)

[0073] Resin composition constituting functional layer B: Polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220°C) 90% by mass; Polyamide MXD6 (manufactured by Mitsubishi Gas Chemical Co., Ltd., relative viscosity 2.1, melting point 237°C) 10% by mass; 0.54% by mass of porous silica microparticles (manufactured by Fuji Silysia Chemical Ltd., average particle size 2.0 μm, pore volume 1.6 ml / g); Fatty acid bisamide (ethylene bis stearic acid amide, manufactured by Kyoeisha Chemical Co., Ltd.) 0.15% by mass

[0074] (Examples 1 to 7) The raw materials for the base layer (A layer) and the functional layer (B layer) were mixed in the formulation shown in Table 1. Using an apparatus consisting of two extruders and a 380 mm wide co-extrusion T-die, lamination was performed using the feed block method in a configuration of functional layer: B layer / base layer: A layer / functional layer: B layer, and the molten resin of the resin composition shown in Table 1 was extruded from the T-die into a film, which was then cast onto a cooling roll whose temperature was adjusted to 20°C and electrostatically adhered to obtain an unstretched film with a thickness of 100 to 200 μm.

[0075] The obtained unstretched film was introduced into a roll-type stretching machine, and using the difference in peripheral speed of the rolls, it was stretched 1.73 times in the MD direction at 80 ° C., and then further stretched 1.85 times at 70 ° C. Subsequently, this uniaxially stretched film was introduced into a tenter-type stretching machine, preheated at 60 ° C., and then stretched 1.2 times in the TD direction at 120 ° C., 1.7 times at 130 ° C., and 2.0 times at 160 ° C., heat-set at 218 ° C., and then 7% relaxation treatment at 218 ° C., and the surface of one side was corona discharge treated to obtain a biaxially stretched polyamide film. The discharge amount of the extruder was adjusted so that the thickness of the base layer was 8 μm and the thickness of the functional layer was 1 μm on each side with respect to the thickness of the biaxially stretched polyamide film of 10 μm.

[0076] (Examples 8 and 9) A biaxially oriented polyamide film was obtained in the same manner as in Examples 1 to 7, except that the feed block configuration and the extruder output were adjusted so that the total thickness of the biaxially oriented polyamide film was 15 μm with the thickness of the base layer being 12 μm and the thickness of the functional layer being 1.5 μm on each side with the composition shown in Table 1.

[0077] (Comparative Examples 1 to 4 and 6) A biaxially stretched polyamide film was obtained in the same manner as in Example 1, except that the resin compositions of the base layer and the functional layer were changed as shown in Table 2. The evaluation results of the obtained film are shown in Table 2.

[0078] Comparative Example 5 Biaxially oriented polyamide films were obtained in the same manner as in Examples 1 to 7 and Comparative Examples 1 to 4 and 6, except that the rotation speed of the extruder that extrudes the resin composition that constitutes the base layer was increased within a range that did not increase the target thickness, and the kneading was strengthened.

[0079] The evaluation results of the films obtained in the examples and comparative examples are shown in Table 1.

[0080] [Table 1A]

[0081] [Table 1B]

[0082] [Table 1C]

[0083] [Table 1D]

[0084] The films described in Examples 1 to 9 had good pinhole resistance, dimensional stability, puncture strength, and ethanol permeability, and were suitable for alcohol evaporative applications. The plane orientation degree was 0.5 or more, which was highly oriented, and the crystallization parameter was 1.0 or more, which was highly crystallized, while the resin (b) was dispersed with a dispersion diameter of 1 μm or more, forming an interface with relatively low adhesion strength with the polyamide resin, and it is believed that this interface was utilized to improve ethanol permeability. Furthermore, it is believed that the flexibility of the base layer A itself was improved by the dispersion of the resin (b), and the pinhole resistance of bending was improved.

[0085] The film described in Comparative Example 1 was excellent in dimensional stability and puncture strength, but was poor in bending pinhole resistance and ethanol permeability. When the plane orientation ΔP was 0.05 or more and the crystallization parameter was in the range of 1 to 1.5, the dimensional stability and puncture strength were good, but it is believed that the progress of crystallization increased the brittleness of the film, causing the pinhole resistance and ethanol permeability to decrease.

[0086] Although the film described in Comparative Example 2 had a thickness of 15 μm, since the base layer contained no resin other than polyamide 6, no dispersion structure was formed due to phase separation, and ethanol permeation did not occur using the dispersion interface, and the ethanol permeability was not satisfactory for use as an alcohol evaporative agent.

[0087] The film described in Comparative Example 3 was as thick as 25 μm, and since no resin other than polyamide 6 was added to the base layer, the pinhole resistance and ethanol permeability were not satisfactory for use as an alcohol vaporizer.

[0088] The film described in Comparative Example 4 had a small amount of PBAT added as the resin (b), and the interface between polyamide 6 and PBAT was small, resulting in insufficient ethanol permeability.

[0089] In the film of Comparative Example 5, the maximum dispersion diameter of the resin (b) was as small as 0.5 μm, and compatibility with polyamide 6 progressed, so that good ethanol permeability and good pinhole resistance were not obtained.

[0090] The film described in Comparative Example 6 had an ethanol permeability of 16000 g μm / m 2 -24hr (50%RH / 40℃). As an ethanol evaporant, the ethanol evaporates faster.

Claims

1. A biaxially oriented polyamide film containing polyamide 6 as a main component, and having an ethanol permeability of 6000 to 10000 g μm / m 2 A biaxially oriented polyamide film having a 24 hr (50% RH / 40°C), a thickness of 15 μm or less, a thermal shrinkage rate of 2.0% or less in both the machine direction and width direction of the film when heat-treated for 10 minutes at 160°C, a surface crystallization parameter in the range of 1.0 to 1.5, and a puncture strength of 6.0 N or more.

2. 2. The biaxially oriented polyamide film according to claim 1, having at least one layer containing 60% by mass or more and 98% by mass or less of a polyamide 6 resin (a) and 2% by mass or more and 40% by mass or less of a resin other than polyamide 6 (b).

3. 3. The biaxially stretched polyamide film according to claim 2, wherein the resin (b) other than polyamide 6 is at least one selected from the group consisting of thermoplastic elastomers such as polyolefins, ionomer polymers, polyester-based elastomers, polyamide-based elastomers, polyolefin-based elastomers, polystyrene-based elastomers, polyurethane-based elastomers, and polyvinyl chloride-based elastomers, aliphatic polyester resins, aliphatic-aromatic polyester resins, aliphatic polyamide resins, and aliphatic-aromatic polyamide resins.

4. 4. The biaxially oriented polyamide film according to claim 3, wherein the aliphatic-aromatic polyester resin is a polybutylene adipate terephthalate resin.

5. 3. The biaxially oriented polyamide film according to claim 2, wherein the resin (b) other than polyamide 6 is derived from biomass and is at least one polyamide selected from the group consisting of polyamide 11, polyamide 410, polyamide 610, and polyamide 1010.

6. 3. The biaxially oriented polyamide film according to claim 2, wherein the maximum dispersion diameter of the resin (b) other than polyamide 6 is 1.0 μm or more.

7. 2. The biaxially oriented polyamide film according to claim 1, wherein the stress at 5% elongation in both the machine direction and the width direction of the film is 70.0 MPa or less.

8. 2. The biaxially oriented polyamide film according to claim 1, having a planar orientation degree (ΔP) of 0.050 or more.

9. 2. The biaxially oriented polyamide film according to claim 1, wherein a laminate film of the biaxially oriented polyamide film and a polyethylene film having a thickness of 40 μm is prepared, and the film is subjected to a bending treatment 1,000 times in an atmosphere at a temperature of 1° C. using a Gelbo flex tester. The biaxially oriented polyamide film according to claim 1, wherein the number of pinholes generated is 20 or less.

10. A food packaging material comprising the biaxially oriented polyamide film according to any one of claims 1 to 9 and a sealant film.

11. A packaging material for an ethanol transpiration agent, comprising a laminate including at least two layers of the biaxially oriented polyamide film according to any one of claims 1 to 9 and a breathable resin film or nonwoven fabric.

Citation Information

Patent Citations

  • Stretched polyamide film and method for producing the same

    JP2010158775A

  • Polyamide laminated film with excellent permeability to water vapor and alcohol

    JP2010167652A

  • Alcohol-permeable polyamide film

    JP2010241901A

  • Polyamide resin film and package using the film

    JP2021130770A

  • Laminate film

    JP2022169513A